Biochemistry - Voet, Donald (John Wiley & Sons, 2004)
Biochemistry 3rd edition DONALD VOET, University of Pennsylvania, USA and JUDITH G. VOET, Swarthmore College, USA Biochemistry is a modern classic that has been thoroughly revised. Don and Judy Voet explain biochemical concepts while offering a unified presentation of life and its variation through evolution. Incorporates both classical and current research to illustrate the historical source of much of our biochemical knowledge. ∗ This edition has been updated to reflect the enormous advances in molecular and protein structure ∗ Integrated Biochemical Interactions CD